Reproductive Performance of Multiparous Ewes with Different Flushing Ration Manage-ment: Reproductive Performance of Multiparous Ewes after Flushing Ration Management - Triansyah, Irvan; Astuti, Dewi Apri; Arifiantini, R. Iis (IPB University, 2025)
Local sheep are small ruminants that are kept by many farmers. The reproductive success of the animals is influenced by the ration offered. The aim of this study is to evaluate the reproductive performance of multiparous ewes with different flush management. For the study, 16 multiparous ewes were used in a 4 x 4 randomized group design. Treatments consisted of P1 = no flushing, P2 = flushing before and after mating, P3 = flushing before and after mating and at mid-pregnancy, P4 = flushing before and after mating, at mid-pregnancy and at the end of pregnancy. The variables observed were the percentage of pregnancy, number of embryos, embryo diameter, amnion diameter, embryo durability, number of offspring and duration of pregnancy. The results showed that the management of flushing rations influenced the pregnancy rate and amniotic diameter. The number and diameter of embryos, gestation length, number of offspring and embryo lifespan did not differ between treatments (P>0.05). This study concludes that the management of flushing rations affects reproductive performance in terms of pregnancy rate and amniotic diameter.